1968
DOI: 10.1346/ccmn.1968.0160402
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Clay in Poultry Feed

Abstract: Abstract-Dietary clay supplements (bentonite and kaolinite) have been used as binding and lubricating agents in the production of pelleted feeds for chickens. The high-swelling and water absorbing capacity of some bentonites make them attractive dietrary additives for control of wet droppings in caged layers. In addition, experiments show that layers fed on these diets exhibit significant increases in body weight, egg size, and life expectancy even though their total caloric intake is less than that of the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
4

Year Published

1977
1977
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 3 publications
2
15
0
4
Order By: Relevance
“…Increased uptake of particle-bound prions might explain enhanced oral transmissibility. Alternatively, aluminosilicates may increase residence time of agent in the digestive system (Bringe & Schultz, 1969; Collings et al, 1980; Quisenberry, 1968) and elevate exposure time at sites of conversion. Further investigation into these mechanisms, the effect of digestive processes on bound prions, and alterations of agent physicochemical properties upon binding is warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased uptake of particle-bound prions might explain enhanced oral transmissibility. Alternatively, aluminosilicates may increase residence time of agent in the digestive system (Bringe & Schultz, 1969; Collings et al, 1980; Quisenberry, 1968) and elevate exposure time at sites of conversion. Further investigation into these mechanisms, the effect of digestive processes on bound prions, and alterations of agent physicochemical properties upon binding is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Further, aluminosilicates increase residence time of feed in the digestive system (Bringe & Schultz, 1969; Collings et al, 1980; Quisenberry, 1968), preserve consumed nitrogen in usable forms for rumen bacteria (Mumpton, 1999), and aid in drug delivery (Byrne & Deasy, 2005). Johnson et al (2007) previously reported that the aluminosilicate mineral Mte increased the oral transmissibility of a low dose of prions by a factor of 680.…”
mentioning
confidence: 99%
“…Since 1965, experiments have been in progress in Japan on the use of natural zeolites as dietary supplements for poultry, swine and cattle. Based on the successful use of montmorillonite clay in slowing down the passage of nutrients in the digestive system of chickens and the resultant improvement in caloric efficiency, as reported by Quisenberry (1968), clinoptilolite and mordenite have been added to the normal protein diets of pigs, chickens, and ruminants at several agricultural stations and livestock farms in Japan. Significant increases in the gain of body weight per unit of feed consumed (feed efficiency) and in the "general health" of the animals have been achieved (Minato, 1968).…”
Section: Animal Nutritionmentioning
confidence: 99%
“…In addition, diatomaceous earth affects body detoxification and bowel purgation (also from residues of veterinary pharmaceuticals), which increases feed intake by animals. What is more, according to other researchers, the intake of fine-grain feed additives may improve absorption of nutrients in poultry (Quisenberry 1967, van der Meulen et al 2008.…”
Section: Resultsmentioning
confidence: 90%
“…Diatomaceous earth (diatomite) is a natural sedimentary rock, formed mainly by fossilized frustules of diatoms -single-celled algae. These organisms had lived many millions years ago in the aquatic environment, and then -as a result of successive drying out of water bodies -they have formed deposits of diatomaceous earth (Round et al 1990). As reported by Fields (2000), the frustules of diatoms in diatomite are built mainly of silica (SiO 2 ) and trace amounts of other mineral compounds, like: aluminum, iron oxide, lime, magnesium or sodium.…”
Section: Introductionmentioning
confidence: 99%